Physico-chemical characteristics of some guava varieties in Malaysia. - Yusof, Salmah (1989)
A study was conducted to compare the physico-chemical characteristics of some guava varieties found in Malaysia. Ten mature fruits (pressure reading = 8kg-10kg) of varieties Gu4, Gu5, Gu7, Hongkong pink, Jambu Biji, Taiwan, Laknaw and Vietnamese were used for the study. The physical and chemical analysis conducted were weight, diameter, mesocarp thickness, pulp : seed ratio, total soluble solids content, pH, titratable acidity and ascorbic acid content. Results indicated thet most of the local varieties (Gu4, Gu5, Gu7, Jambu Biji and Hongkong pink) were smaller in size 4.8cm-6.7cm diameter) and had thinner mesocarp (0.9cm-1.5cm) compared to the newly introduced Vietnamese variety which had a diameter and mesocarp thickness measurements of 10cm-11cm and 1.9cm-2.5cm, respectively. The mesocarp colour of the guavas varied from pink to the red or white. The moisture content of the fruits ranged from 79.2%-85.9%. The total soluble solids were less than 9%. The pH and titratable acidity ranged from 3.89-4.1 and 0.26%-0.52%, respectively. The vitamin C content varied from 40.1 mg/g - 180.5 mg/100g.